Chemoradiation in Unresectable Oral Cavity Cancer: A Myth or Reality! - Patil, Vijay Maruti; Noronha, Vanita; Joshi, Amit; Kumar, Amit; Dsouza, Hollis; Bhattacharjee, Atanu; Mahajan, Abhishek; Sabale, Nilesh; Ghosh-Laskar, Sarbani; Prabhash, Kumar (South Asian Journal of Cancer, 2020)
Objective Earlier studies have shown that chemoradiation (CTRT) has benefits in the head-and-neck cancer, but how far it is true for oral cavity subset that has not been exactly explored. Keeping the null hypothesis as CTRT has no benefit in oral cavity cancer, we studied the outcome of patients undergoing chemoradiation in unresectable oral cavity cancers. The aim of this study is to study whether overall survival (OS) increases with chemoradiation in unresectable oral cavity cancers.Patients and Methods Between December 2014 and February 2017, 23 patients aged 18 years and above were planned chemoradiation for unresectable oral cavity cancer and were included for this analysis.Results The median age of patients was 43 years and all patients were addicted to tobacco. In total, 12 of 23 (52%) completed CTRT. One patient (1/23) was alive at the time of final analysis with median OS of 5.83 (2.73–9.60) months. The median progression free survival and OS in patients who completed chemoradiation were 6.42 months (95% confidence interval [CI]: 3.67–10.53) and 8.9 months (95% CI: 4.4–23.07), respectively.Conclusion CTRT has a limited role in unresectable oral cancers.
Keywords: borderline resectable; chemoradiation; oral cancer; unresectable